Large Swings in Currencies driven by Fundamentals - Phornchanok Cumperayot; Casper G. de Vries (Tinbergen Institute, 2006)
Exchange rate returns are fat-tailed distributed. We provide evidence that the apparent non-normality derives from the behavior of macroeconomic fundamentals. Economic and probabilistic arguments are offered for such a relationship. Empirical support is given by testing against normality and through investigating the tail shapes of the fundamentals' distributions. The currently available data sets on floating exchange rates permit a clearer picture than the relatively short spans with macroeconomic data available previously.
Keywords: E44; F31; 330; exchange rates; fundamentals; fat-tailed distributions